Distinct exercise modalities on GUT microbiome in sarcopenic older adults: study protocol of a pilot randomized controlled trial - Merelim, Ana Sofia; Zacca, Rodrigo; Moreira-Gonçalves, Daniel; Costa, Paulo P.; Baptista, Liliana C. (Frontiers in Medicine, 2025)
BackgroundSarcopenia is a progressive and age-related skeletal muscle disease related to adverse health outcomes and to an increased economic burden. Recent evidence pinpoints the human gut microbiota (GM) as a contributing factor in the development of sarcopenia via the gut-muscle axis. To date, no study specifically analyzed the optimal type of exercise modality in older adults with sarcopenia considering the impact of GM composition in skeletal muscle mass and function. Therefore, the DEMGUTS study intents to explore the impact of three different exercise regimens on GM composition and gut-derived metabolites in older adults with sarcopenia.MethodsThis pilot single center three-arm parallel open-label randomized control trial (RCT) will randomly assign eligible participants to: (i) moderate aerobic exercise (AER); (ii) resistance exercise (RES); or (iii) concurrent exercise training (RES + AER). Participants will engage in a supervised center-based exercise intervention (12-weeks, 3 d/week, 60 min/d), and will be assessed at (i) baseline, (ii) end of intervention (14 weeks), and (iii) at close-out (26-weeks). The primary outcome will be the change in the relative abundance of Faecalibacterium prausnitzii and other short-chain fatty acid producing bacteria after the intervention (14-weeks). A set of complementary outcomes will also be assessed to broadly characterize the impact of each exercise intervention on body composition, skeletal muscle function, functional performance and general GM composition.ConclusionUnraveling the impact of these exercise regimens on GM is crucial to help clarify the optimal exercise modality to manage sarcopenia disease, contributing to clinical guidance and enhancing exercise prescription in older adults with sarcopenia.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT06545123.